FRI0207 Prevalence of Femoroacetabular Impingement in Caucasians Compared to Chinese in Vancouver, Canada: A Population-Based Study. (10th June 2014) - Li, L.C.; Kopec, J.A.; Wong, H.; Qian, H.; Cibere, J.; Sayre, E.C.; Zhang, C.; Barber, M.; Ye, J.; Prlic, H.; Esdaile, J.M.
Abstract : Background: Femoroacetabular Impingement (FAI) is one source of hip pain in young adults and has been suggested as a major cause of hip osteoarthritis (OA). The prevalence of radiographic hip OA in the Caucasian population is approximately 5% among people over the age of 65. In Chinese, hip OA is extremely rare. It is, however, unclear if the same trend exists in the prevalence of FAI between populations. Objectives: To describe and compare the prevalence of FAI among Caucasian and Chinese in Vancouver, Canada (population=2.3 million, 2011 Census), where 19% of the population are ethnic Chinese. Methods: This study was conducted within IMPAKT-HiP, a large multi-faceted study on the role of FAI and physical activity in cartilage damage and hip pain. Participants were recruited in a cross-sectional telephone survey of a random sample of residents in Vancouver. Individuals were eligible if they were age 20-49, reported both parents were Caucasian/Chinese descent, and were available for an onsite assessment and x-ray session. Pregnant women were excluded. All calls were initiated in English. Non-English-speaking Chinese respondents received a second call by an interviewer fluent in Mandarin and Cantonese to assess eligibility. All hip x-rays were read by a trained reader using a standardized protocol. The reader was blinded for participants' ethnicity. Pincer-type FAI was defined by: 1) presence of focal acetabular retroversion or 2) a lateral center edge angle >40 degrees. Cam-type FAI was defined by an alpha angle >55 degrees. Results: 500 Caucasians and 200 Chinese (87 English-speaking, 113 Mandarin/Cantonese-speaking) were recruited between March 2012 and May 2013. The majority were women (Caucasians: 64.2%; Chinese: 66.5%) and in the 40-49 years age group (Caucasians: 68.2%; Chinese: 60.5%). Among Caucasians, 112/179 men (62.6%) and 119/321 women (37.1%) had FAI. FAI was found in 33/67 men (49.3%) and 45/133 (33.8%) women in the Chinese population. Unilateral FAI was present in 11.8% Caucasians and 11.5% Chinese, and bilateral FAI in 34.4% Caucasians and 27.5% Chinese. Pincer FAI was the most common (Caucasians: 24.8%, Chinese: 29.5%), followed by cam FAI (Caucasians: 15.2%, Chinese: 7%) and mixed FAI (Caucasians: 6.2%, Chinese: 2.5%). The population-weighted, age/gender-standardized prevalence of FAI was 50.2% (95% CI: 42.9%, 57.5%) for Caucasians and 44.7% (95% CI: 36.7%, 52.7%) for Chinese. Conclusions: This is one of the first population-based studies that directly compared the prevalence of FAI in ethnic groups with different OA prevalence. Although there was a trend that FAI was more common in Caucasians than in the Chinese population, the difference was not statistically significant. Further research to examine prevalence of FAI in populations with high (e.g., Aboriginal populations) vs. low hip OA prevalence may provide further insight into the cause of hip OA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3947